Correlation of atorvastatin with subjective memory deficits: a study from the NHANES and FAERS databases - Zhang, Hao; Huang, Hua; Zhao, Panli (Frontiers in Neurology, 2025)
BackgroundPost-marketing regulatory data suggest a potential association between atorvastatin use and memory protection; however, findings from observational studies have been inconsistent and remain a subject of controversy.ObjectiveThis study aims to investigate the correlation between atorvastatin exposure and subjective memory deficits, with the objective of providing more precise safety and efficacy information for its clinical use.MethodsWe utilized two primary data sources: the National Health and Nutrition Examination Survey (NHANES) covering the years 2001 to 2018, and the Food and Drug Administration Adverse Event Reporting System (FAERS) spanning 2011 to 2018. We systematically analyzed the correlation between atorvastatin exposure and memory function using a range of statistical methods, including descriptive statistics, multivariate logistic regression, and receiver operating characteristic (ROC) curves.ResultsIn the analysis of the NHANES database, multivariate logistic regression modeling, after controlling for various factors such as demographic characteristics and lifestyle, revealed a significant association between atorvastatin use and a reduced risk of memory loss (OR = 0.47; 95% CI, 0.15–0.79; p = 0.004). This suggests that atorvastatin may offer a protective effect on memory. Conversely, our analysis of the FAERS database identified 15,277 reports of adverse reactions associated with atorvastatin, of which 401 were related to psychiatric adverse events, including memory loss. This finding indicates that while atorvastatin may not generally increase the risk of memory loss, some patients may still experience these side effects.ConclusionThis study integrated data from NHANES and FAERS to provide a comprehensive analysis of the relationship between atorvastatin and memory function. On one hand, the NHANES findings support the potential benefits of atorvastatin in reducing the risk of memory loss. On the other hand, the FAERS data highlight specific cognitive side effects associated with the drug. Consequently, clinicians and patients should carefully consider both the potential benefits and risks of atorvastatin, taking into account individual patient differences and implementing appropriate monitoring strategies.